Is antibiotic prophylaxis expendable in parotid gland surgery?: A retrospective analysis of surgical site infection rates - Hohenberger, Ralph; Bremer, Isabel; Krisam, Regina; Plinkert, Peter K.; Federspil, Philippe A. (Clinical otolaryngology, 2021)
Objectives To evaluate the rate of surgical site infection (SSI) and associated risk factors after parotid gland surgery including the impact of antibiotic prophylaxis. Design Retrospective single-centre clinical study. Setting Tertiary referral centre for head and neck surgery. Participants Seven hundred and fifty four patients who underwent parotid gland surgery at the University Hospital Heidelberg, Germany, between 2007 and 2014 were enrolled in this study. Data on patient age, American Society of Anesthesiologists (ASA) classification system, smoking status, diabetes mellitus, operation time, and antibiotic prophylaxis were collected. Additionally, the National Healthcare Safety Network (NHSN) risk index was calculated. Association of these factors with SSI was evaluated in univariate analyses and a multivariate logistic regression model. Main outcome measures Rate of SSI. Results Twenty four patients (3.2%) had an SSI according to the NHSN definition. In univariate analyses, only smokers (P = .048) and male patients (P = .01) had a significantly higher rate of SSI. Since the majority of smokers were men (62.3%), the effect of male gender, smoking, together with the NHSN risk index was further investigated as predictors of SSI within a logistic regression model. All three predictors showed a significant effect on SSI. Conclusions Parotid gland surgery has a low rate of SSI. In our cohort, male gender, smoking and high NHSN risk index scores were significantly associated with SSI, whereas antibiotic prophylaxis had no protective effect.
Gesehen am 28.11.2022